2022
DOI: 10.26493/2590-9770.1494.1e4
|View full text |Cite
|
Sign up to set email alerts
|

Some Erdös-Ko-Rado results for linear and affine groups of degree two

Abstract: In this paper, we show that both the general linear group GL(2, q) and the special linear group SL(2, q) have both the EKR property and the EKR-module property. This is done using an algebraic method; a weighted adjacency matrix for the derangement graph for the group is found and Hoffman's ratio bound is applied to this matrix. We also consider the group AGL(2, q) and the 2-intersecting sets in PGL(2, q)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…It is well known (see [2] or [3], for example) that, since G n contains a Singer cycle as a regular subgroup, the size of every 1-intersecting set in G n is at most the expression given in (1•1) for t = 1. Meagher and Razafimahatratra [21] have shown that, if Y is a 1-intersecting set of size q 2 − q in G 2 , then 1 Y is in the span of the characteristic vectors of the 1-cosets. We prove a corresponding result for all t and n for which n is sufficiently large compared to t. THEOREM 1•1.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…It is well known (see [2] or [3], for example) that, since G n contains a Singer cycle as a regular subgroup, the size of every 1-intersecting set in G n is at most the expression given in (1•1) for t = 1. Meagher and Razafimahatratra [21] have shown that, if Y is a 1-intersecting set of size q 2 − q in G 2 , then 1 Y is in the span of the characteristic vectors of the 1-cosets. We prove a corresponding result for all t and n for which n is sufficiently large compared to t. THEOREM 1•1.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Meagher and Sin [23] recently showed that all finite 2-transitive groups have the EKR-module property. However, the strict-EKR property does not hold for permutations groups in general; recently, Meagher and Razafimahatratra [22] have shown that the general linear group GL(2, q) is such a counterexample. We remark that our results are of similar flavor, although in our context of Peisert-type graphs, the corresponding vector space W does not carry a natural module structure.…”
Section: Ekr-type Resultsmentioning
confidence: 99%
“…In [17], a measure for intersecting sets in transitive groups was introduced. Formally, the intersection density of a transitive group G ≤ Sym(Ω) is the rational number ρ(G) := max {ρ(F ) | F ⊂ G is intersecting} , where ρ(F ) := |F | |Gω| for any intersecting set F and G ω is the point stabilizer of ω ∈ Ω in G. The study of intersection density in transitive groups has recently drawn the attention of many researchers [1,11,12,13,18,19,21,22,20,24,26].…”
Section: Introductionmentioning
confidence: 99%